Identification of Novel Clostridium perfringens Type E Strains That Carry an Iota Toxin Plasmid with a Functional Enterotoxin Gene - Miyamoto, Kazuaki (Public Library of Science, 2011)
Clostridium perfringens enterotoxin (CPE) is a major virulence factor for human gastrointestinal diseases, such as food poisoning and antibiotic associated diarrhea. The CPE-encoding gene (cpe) can be chromosomal or plasmid-borne. Recent development of conventional PCR cpe-genotyping assays makes it possible to identify cpe location (chromosomal or plasmid) in type A isolates. Initial studies for developing cpe genotyping assays indicated that all cpe-positive strains isolated from sickened patients were typable by cpe-genotypes, but surveys of C. perfringens environmental strains or strains from feces of healthy people suggested that this assay might not be useful for some cpe-carrying type A isolates. In the current study, a pulsed-field gel electrophoresis Southern blot assay showed that four cpe-genotype untypable isolates carried their cpe gene on a plasmid of ∼65 kb. Complete sequence analysis of the ∼65 kb variant cpe-carrying plasmid revealed no intact IS elements and a disrupted cytosine methyltransferase (dcm) gene. More importantly, this plasmid contains a conjugative transfer region, a variant cpe gene and variant iota toxin genes. The toxin genes encoded by this plasmid are expressed based upon the results of RT-PCR assays. The ∼65 kb plasmid is closely related to the pCPF4969 cpe plasmid of type A isolates. MLST analyses indicated these isolates belong to a unique cluster of C. perfringens. Overall, these isolates carrying a variant functional cpe gene and iota toxin genes represent unique type E strains.